The Influence of Bank Indonesia Rate and Bank Size on Return on Assets in Sharia Banking in Indonesia 2019-2022 - Hidayat, Faris Rahman Nur; Sumanto, Agus (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
The purpose of this study is to ascertain how the Bank Indonesia Rate and Bank Size will affect the ROA (Return on Assets) of Islamic Banking in Indonesia from 2019 to 2022. The study used quantitative techniques, specifically the use of secondary data obtained through the website of the Financial Services Authority (OJK), as well as the website of Bank Indonesia. The results of this study indicate that Bank Indonesian Rate partially has a negative and significant effect on Return on Assets (ROA), and Bank Size partially has a negative and significant effect on Return on Assets (ROA). Meanwhile, Bank Indonesia Rate and Bank Size simultaneously have a significant and significant effect on Return on Assets (ROA), where the F test findings indicate that the coefficient of determination is 33.2% and another variable (66.8%) not included in this study has a coefficient of determination of 66.8%.